Rainwater Harvesting as Alternative Source Of Sanitation Water In Indonesian Urban Area (Case Study: Bandar Lampung City) - Gatot Eko Susilo (Rekayasa Sipil, 2018)
This paper aims to investigate supporting capacity of rainwater harvesting (RWH) to meet sanitation water needs in the area of Bandar Lampung. Simulation involving rainfall data, house roof data, house dwelling data, and data of domestic water needs per capita is carried out to find optimum supporting capacity of RWH. The simulations show that optimum storage for the RWH in the area of study is 90 m REKAYASA SIPIL / Volume 12, No.1 – 2018 ISSN 1978 - 5658 3 . On this design, supporting capacity of RWH for year 2012, 2013, and 2014 is 71.2%, 99.2%, and 99.7%, respectively. Main advantage of RWH is the preservation of groundwater. Others are the reduction of surface drainage discharge and the reduction of electricity consumption for taking groundwater